Policyjne determinanty w profilowaniu wolnych zawodów - Kocowski, Tadeusz; Małecki, Witold (Studia Prawa Publicznego, 2022)
The possibility of taking up and practising liberal professions is generally dependent on the possession of professional qualiﬁcations, set out in law. The need to obtain certain qualiﬁcations often stems from the necessity to protect such goods as life, health and property. These might be referred to as ‘police goods’. They are existential for the functioning of the state, society and individuals, and are protected within the most important and most signiﬁcant function of the state, which is the police. One of the areas of the police is the economic police, related to the protection of police goods against threats that may arise as a result of economic activity. Among the liberal professions there are those for which the requirements of obtaining certain qualiﬁcations result from the need to protect life and health. These are, in the ﬁrst place, professions whose performance on the basis of appropriate qualiﬁcations guarantees a high level of protection of the life and health of the direct recipients of services provided by a person performing a liberal profession. This applies to the medical professions – doctors, dentists, nurses, midwifes, pharmacists and physiotherapists. Secondly, it is necessary to mention the professions the performance of which on the basis of appropriate qualiﬁcations guarantees a high level of protection of life and health of the undetermined group of persons. These professions include that of the architect and civil engineer. A disputable issue is whether professions whose representatives are to protect their clients against unfavourable or unlawful disposal of their own property can be considered liberal professions, where the requirement to obtain certain qualiﬁcations results from the need to protect police states and goods. These are legal professions, as well as the professions of investment advisor and property appraiser.